FEATURES OF DAMAGE TO THE SHOULDER JOINT IN VOLLEYBALL PLAYERS - Abadan Ismailova (Web of Journals Publishing, 2024)
The article discusses the features of injuries to the shoulder joint in volleyball players.
Keywords: volleyball, shoulder, damage, feature, injury, shock, muscle.